Qualidade da Construção dos Vínculos entre Filhas Cuidadoras e Mães Idosas Dependentes - RUGENE, OLINDA TEREZA (2016)
This study aimed to: - describe the difficulties in relations between the daughters, caregivers and their dependent elderly nursing mothers, from reports of daughters; - investigate, from the accounts of family history of these daughters, the existence of previous conflicts the need to care, related to the construction of the bonds; identify the main challenges associated assistance to family caregivers of elders with respect to conflict resolution with the dependent elderly. Method - treated is a qualitative study that were presented three cases of caregivers who had been referred for psychological care by the professional staff of the Institute of Geriatrics and Gerontology, secondary care unit of the State Secretariat SP Health Results They indicated relational difficulties between the two: caretakers daughters and elderly mother. Caregivers revealed physical and emotional burden and great suffering. However, the existence of these conflicts dating back to previous relations to the current situation of dependence; getting enough evidenced both by the life stories of caregivers, as the content brought during the therapeutic process, the repetition of the first relationships established between mother and daughter. The psychotherapeutic process could allow these caregivers to understand the need to have their environmental failures met, to the extent that propiciávamos an enabling environment for human relationship. Thus, to observe that throughout the process the patients had significant changes, we believe that psychotherapy may be included as a preventive means and preservation of mental balance